What India can learn from globally successful malaria elimination programmes. Issue 6 (27th June 2022) - Sharma, Sachin; Verma, Reena; Yadav, Bhawna; Kumar, Amit; Rahi, Manju; Sharma, Amit
Abstract : India is targeting malaria elimination by 2030. Understanding and adopting the strategies employed by countries that have successfully eliminated malaria can serve as a crucial thrust in this direction for a geographically diverse country like India. This analysis is based on extensive literature search on malaria elimination policies, strategies and programmes adopted by nine countries (China, El Salvador, Algeria, Argentina, Uzbekistan, Paraguay, Sri Lanka, Maldives and Armenia) which have attained malaria-free status over the past decade. The key points which India can learn from their journey are mandatory time-bound response in the form of case reporting and management, rapid vector control response, continuous epidemiological and entomological surveillance, elevated community participation, more training and capacity building, private sector involvement, use of quality diagnostics, cross-border collaborations, inclusion of prevention of re-establishment programmes into the elimination plans, higher investment in research, and uninterrupted funds for successful implementation of malaria elimination programmes. These learnings would help India and other South Asian countries steer their programmes by devising tailor-made strategies for their own regions.